2005
DOI: 10.1128/jb.187.5.1740-1750.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Class 1 Integron andVibrio choleraeSuperintegron Integrase Activities

Abstract: Superintegrons (SIs) and multiresistant integrons (MRIs) have two main structural differences: (i) the SI platform is sedentary, while the MRI platform is commonly associated with mobile DNA elements and (ii) the recombination sites (attC) of SI gene cassette clusters are highly homogeneous, while those of MRI cassette arrays are highly variable in length and sequence. In order to determine if the latter difference was correlated with a dissimilarity in the recombination activities, we conducted a comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 41 publications
1
93
0
Order By: Relevance
“…On their side, it is also possible that MI-integrases show differential properties, such as distinct rates of activity or differences in the range of attC-sites recognized. Broader substrate recognition has indeed been observed to be the case for IntI1 compared with VchIntIA and IntIPstQ from Pseudomonas stutzeri (37,132). It is tempting to speculate that the success of class 1 integrons could be due, at least partly, to IntI1 recognizing a broader variety of attC sites and conferring access to a larger portion of cassette-encoded functions.…”
Section: On the Success Of Mismentioning
confidence: 99%
See 2 more Smart Citations
“…On their side, it is also possible that MI-integrases show differential properties, such as distinct rates of activity or differences in the range of attC-sites recognized. Broader substrate recognition has indeed been observed to be the case for IntI1 compared with VchIntIA and IntIPstQ from Pseudomonas stutzeri (37,132). It is tempting to speculate that the success of class 1 integrons could be due, at least partly, to IntI1 recognizing a broader variety of attC sites and conferring access to a larger portion of cassette-encoded functions.…”
Section: On the Success Of Mismentioning
confidence: 99%
“…It has been observed that, contrary to the class I integron system, which recombines equally in E. coli and V. cholerae, the VchIntIA integrase of the V. cholerae CI recombines at a 2,600-fold higher rate the VCR sites in its original genomic background than in E. coli strains (37). Such results suggest either the involvement of one or more host factors in V. cholerae that would be absent or too divergent in E. coli strains, or the presence of an inhibitory factor in E. coli.…”
Section: Accessory Host Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used excision assays (Collis & Hall, 1992;Drouin et al, 2002; Léon & Roy, 2003) or cointegrate assays (Biskri et al, 2005;Collis et al, 2002Collis et al, , 2001Holmes et al, 2003b;Martinez & de la Cruz, 1988) to quantify integron recombination. Improvements to these assays include the use of mobilizable suicide plasmids to deliver single-stranded recombination templates , and using quantitative PCR to simplify the cointegrate assay (Shearer & Summers, 2009;Wei et al, 2011;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Integrons are common in bacteria, and diverse in their phylogeny and predicted functions (Boucher et al, 2007a; Elsaied et al, 2007;Gillings et al, 2005;Holmes et al, 2003a;Nield et al, 2001;Rowe-Magnus & Mazel, 2001;Rowe-Magnus et al, 2003). Integrons increasingly seem to have a role as general-purpose agents of adaptation, not just enablers of antibiotic resistance (Koenig et al, 2009(Koenig et al, , 2011Rosewarne et al, 2010;Wright et al, 2008).Previous studies have used excision assays (Collis & Hall, 1992;Drouin et al, 2002; Léon & Roy, 2003) or cointegrate assays (Biskri et al, 2005;Collis et al, 2002Collis et al, , 2001Holmes et al, 2003b;Martinez & de la Cruz, 1988) to quantify integron recombination. Improvements to these assays include the use of mobilizable suicide plasmids to deliver single-stranded recombination templates , and using quantitative PCR to simplify the cointegrate assay (Shearer & Summers, 2009;Wei et al, 2011;Yang et al, 2009).…”
mentioning
confidence: 99%